Professional Japanese Tour Guides and Its Implications on Japanese Teaching Development for Tourism Students - Devita Widyaningtyas Yogyanti; Angela Bayu Pertama Sari; Dwi Iswahyuni (Universitas Diponegoro, 2020)
In line with the significance of appropriate Japanese learning methods and materials for tourism students, this study investigates how Japanese tour guides in Indonesia learn Japanese. This study aimed to find out some factors which influenced the process of Japanese tour guides’ second language acquisition and the integration of those factors into Japanese teaching. This study was a qualitative study with ethnography method approach. Interviews and observation were employed in this study as the research instruments in which 12 Japanese tour guides became the research objects. The findings showed that two main factors influenced the process of Japanese tour guides’ second language acquisition, namely intrinsic factors and extrinsic factors. Intrinsic factors were the factors which emerged within the tour guides themselves that affected the success of the language acquisition such as age, motivations, personality, aptitudes and the attitudes towards the Japanese language. Meanwhile, the extrinsic factors encompassed learning styles and teaching method that determined the success of language acquisition. Furthermore, the integration of those factors into the Japanese teaching generated some focuses on the teaching process, which were speaking fluently and interacting easily. Speaking fluently put more emphasis on the fluency rather than grammar mastery, while interacting easily was related to the implementation of intercultural language teaching.